COMPARING THE EFFICACY OF ROM EXERCISES WITH AND WITHOUT SCAPULAR MOBILIZATION IN PATIENTS WITH ADHESIVE CAPSULITIS - KHANDELWAL, PINKY; KHAN, JAFAR; P. T., RENUKA; KHAN, USMAN (International Journal of Current Pharmaceutical Research, 2023)
Objective: Adhesive capsulitis, or frozen shoulder, is a condition characterized by shoulder pain and limited range of motion. Its cause and pathophysiology are not well understood. The prevalence is estimated to range from 2% to 5% in the general population, with a higher incidence in women and individuals in their fifth and sixth decades of life. The optimal treatment approach for adhesive capsulitis is currently unclear, although ROM exercises are commonly prescribed. Scapular mobilization may enhance outcomes by addressing scapular dyskinesis and muscle imbalances. Methods: A comparative study with 30 subjects diagnosed with adhesive capsulitis was conducted. Subjects were randomly assigned to two groups: ROM exercises with scapular mobilization (Group 1) and ROM exercises without scapular mobilization (Group 2). The study took place at PMCH, Udaipur, for 12 w, with sessions lasting 30 min per day, 5 d a week. Inclusion and exclusion criteria were established, and outcome measures such as pain scores, ROM measurements, functional assessments, and patient-reported outcomes were used. Results: The analysis of SPADI scores revealed that Group A had a mean score of 41.73 (SD = 4.69, SE = 0.86), while Group B had a mean score of 42.40 (SD = 3.29, SE = 0.84), with a mean difference of 0.67. The t-test indicated a significant difference between the groups (t = 1.335, p = 0.021). Similarly, for VAS scores, Group A had a mean score of 3.20 (SD = 0.67, SE = 0.17), Group B had a mean score of 3.06 (SD = 0.70, SE = 0.18), with a mean difference of 0.14. The t-test also revealed a significant difference between the groups (t = 5.95, p = 0.038). These results demonstrate notable distinctions in both SPADI and VAS scores between Group A and Group B. Conclusion: The study supports the effectiveness of combining scapular mobilization with ROM exercises for adhesive capsulitis. The group receiving both interventions showed greater improvements in shoulder range of motion and pain reduction compared to the ROM exercises alone group. Incorporating scapular mobilization into the treatment approach may enhance the management of adhesive capsulitis. Further research is needed to validate these findings and customize treatments based on individual patient characteristics.